1990
DOI: 10.3109/01485019008986880
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of High Altitude-Induced Testicular Disturbances by Previous Treatment With Cyproheptadine in Male Rats

Abstract: Male rats were exposed to 4,340 m altitude for 4 days. At this time histological alteration in the testes were observed. There were tubules with pyknotic primary spermatocytes and spermatids, necrosis of numerous cells, and sloughing of primary spermatocytes. The damaged areas were limited by normal tissue. Serum testosterone increased significantly after 4 days of exposure. Administration of an anti-serotoninergic compound, cyproheptadine (10 mg/kg body weight), prevented the high altitude-induced changes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
5

Year Published

2001
2001
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 9 publications
0
16
0
5
Order By: Relevance
“…It is known that exposure to high altitude results in damage to spermatogenesis in humans (Donayre 1968) and other animals (Gonzales et al 1990, Saxena 1995. The present study demonstrated that exposure of male rats to an altitude of 4340 m for a period of 21 days resulted in low epididymal sperm count.…”
Section: Discussionmentioning
confidence: 47%
See 4 more Smart Citations
“…It is known that exposure to high altitude results in damage to spermatogenesis in humans (Donayre 1968) and other animals (Gonzales et al 1990, Saxena 1995. The present study demonstrated that exposure of male rats to an altitude of 4340 m for a period of 21 days resulted in low epididymal sperm count.…”
Section: Discussionmentioning
confidence: 47%
“…Spermatogenic arrest induced by high altitude may be due to an increased serotonergic activity (Gonzales et al 1990). Furthermore, serotonin has been demonstrated to affect spermatogenesis by acting directly on the testis (Hedger et al 1995), and it has been shown that hypoxia may increase serotonin levels (Awabdy et al 2003).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations